Molluscicidal Activity and Screening of Forty Egyptian Medicinal Plants and Determination of the Active Fractions - A. Shams, Khaled; M. Abou- Setta, Lobna; M. Radwan, Hany; M. Nazif, Naglaa; A. Hassan, Rasmia; M. Soliman, Abdel-Mohsen (Asian Journal of Chemistry, 2012)
Schistosomiasis is considered as one of the most important trematode diseases of man. The most important goal of the present study is to use the natural plants as low cost and available sources for snail control. Screening of the molluscicidal activity for 40 Egyptian plants were carried out. Only 10 plants showed promising results, Acacia nilotica, Lycopersicum esculentum, Ambrosia maritima, Zizyphus spina-christi, Coronopus squamatus, Diplotaxis acris, Spathodea campanulata, Eruca sativa, Cakile maritima, Nerium oleander showed marked activity. The last 5 plants showed this activity for the first time.